ISLAM SEBAGAI OBJEK STUDI DAN PENELITIAN DARI PENDEKATAN KEILMUAN - Syafrianto, Syafrianto; Efendi, Marhadi; Kamal, Tamrin; Hakim, Rosniati; Julhadi, Julhadi (Ensiklopedia of Journal, 2025)
Islamic studies include the study of Islam as a religion and all aspects related to the lives of Muslims. Islam attracts the attention of both Muslims and non-Muslims to be researched from various points of view, thus making it an object of scientific study. Islamic sciences include branches that are directly related to Islamic teachings, such as Ulumul Quran, Ulumul Hadith, Kalam Science, Fiqh Science, and Sufism. Apart from that, there are natural sciences that were born from the Koran's encouragement to investigate the universe, such as biology, physics and astronomy, as well as social sciences and humanities that study humans and their relationships with each other, such as anthropology, sociology and psychology. This variety of study objects has given rise to diverse methods and approaches in the study of Islam. In conclusion, Islam has become a broad object of study because the Koran and Hadith are not only sources of teaching, but also the basic foundation of science.Some of these Islamic sciences are directly related to the implementation of the teachings of Islam as a religion contained in the Koran and the Hadith of the Prophet Muhammad. such as the Sciences of the Koran (Ulumul Quran), Ulumul Hadith, Kalam Science, Fiqh Science, Sufism; there are also those related to the universe as indicated by the Koran to pay attention to and investigate the universe created by Allah, which then gave birth to natural sciences, such as biology, physics, chemistry, astronomy, geography, and others. Keywords: Islamic Studies, Islamic Science, Ulumul Quran, Social Sciences, Natural Sciences, Study Methods, Al-Quran, Hadith